Textiles and Clothing Sustainability Implications in Textiles and Fashion - Muthu, Subramanian Senthilkannan (Textile Science and Clothing Technology, 2017)
This book comprehensively covers the topic of sustainability in the clothing and fashion sector. Sustainability is applied under different industrial sectors and there has to be a distinction in every industrial sector when it comes to sustainability in its application. Though the definition is common for sustainability, sustainability in the clothing sector has its unique objectives, principles, and limitations, which this book highlights.